Energy-Efficient RIS-Aided Laser-Based LiFi System with Dynamic Coverage Optimization - Huang, Yifan; Papanikolaou, Vasileios; Ajam, Hedieh; Safari, Majid; Schober, Robert; Haas, Harald; Tavakkolnia, Iman (IEEE International Conference on Communications, 2025)
Achieving high-speed optical wireless communication (OWC) with efficient energy usage and full coverage in dynamic environments remains a significant challenge, particularly due to misalignment issues caused by user mobility and random receiver orientations. To address these challenges, this study introduces an innovative reconfigurable intelligent surfaces (RIS)-assisted laser-based light-fidelity (LiFi) system enhanced for energy efficiency and comprehensive coverage. An algorithm is developed to optimize the placement of RIS, reducing the need for continuous real-time adjustments and decreasing system complexity. Moreover, this study introduces a novel power allocation algorithm for multi-tier access points (APs) designed to reduce power consumption. Numerical results demonstrate the superiority of the proposed algorithm over previous designs in terms of transmitted power and outage probability.
CRIS-Team Scopus Importer:2025-10-24